Factors Associated With Dementia In The Elderly At Cakung District Health Center In 2020 - Virrisya Tania, Tasya; Susanti, Fajar; Ifadah, Erlin; Sunadi, Apri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2021)
Dementia is an acquired intellectual and memory dysfunction caused by brain disease, and is not associated with impaired levels of consciousness. The purpose of this study was to determine the factors associated with dementia in the elderly at the Cakung District Health Center in 2020. This study is a quantitative study with a correlative descriptive research design with a cross sectional study approach. The population consisted of elderly patients who participated in prolanis activities at the Cakung District Health Center. Sampling using total sampling. The sample consisted of 60 respondents. Data analysis using chi square test. The results showed a relationship between age (p = 0.000), physical activity (p = 0.000) and dementia. Physical activity needs to be done by the elderly to inhibit the factors that accelerate the onset of dementia. Counseling and learning about physical activity in the elderly should be a program in providing health services to the elderly, especially to prevent dementia. Keywords : Dementia, Physical Activity